(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2025)
This study effect of graded levels of raw Baobab (Adansonia digitata) seed meal on the performance of broiler chickens. 200-day-old broiler chicks were randomly assigned to five treatment groups, each consisting of 40 chicks, with four replicates (10 chicks per replicate) in a completely randomized design. The dietary treatments included different inclusion levels of raw baobab seed meal (RBSM) at 0%, 10%, 20%, 30%, and 40%. The proximate analysis of the raw baobab seed meal revealed a crude protein content of 32.25% and a crude fibre content of 7.10%. The results showed that the final body weight of chickens on the control diet was significantly higher (1344.40 g, p < 0.05) compared to those fed the treatment diets (RBSM). The chickens consuming RBSM had a poorer feed conversion ratio of ranged from 3.50 – 4.54. Moreover, key carcass characteristics, internal organ weights, and haematological indices were also significantly affected (p < 0.05).